Predicting valuable missense variants with AlphaMissense in a multiple pulmonary infection patient - Tianyuan Wang; Jindi Ma; Yuan Shu; Bao Hong; Zhouhan Wang; Yingfeng Lu; Xiaopeng Yu; Xi Huang; Yimin Zhang (Clinical Case Reports, 2024)
Key Clinical Message AlphaMissense is proficient in predicting the clinical classification of missense variants. we utilized AlphaMissense to find disease‐relevant variants within a polymicrobial pulmonary infection case. Exome sequencing was performed in this patient, and AlphaMissense and Phenolyzer were combined to investigate disease‐relevant variants screening from exome sequencing results.